BATASAN DAN IMPLIKASINYA TERHADAP TINDAK PIDANA KORUPSI - Mohamad Ikbal Kadir; Nur Ain Zakaria; Kiran Kiran (LPPM Universitas Muhammadiyah Gorontalo, 2026)
This study examines the boundaries of corruption offenses and their implications for law enforcement and state loss recovery within the framework of anti-corruption character education. The study employs a normative legal approach by analyzing statutes, court decisions, and relevant scholarly literature to identify the line between administrative errors and conduct that fulfills the elements of corruption. The findings indicate that the clarity of unlawful conduct, self-enrichment, benefit elements, and proof of state losses are crucial in determining whether an act should properly be classified as a corruption offense. In addition, reversed burden-of-proof mechanisms and compensation payments play strategic roles, but they must still be applied while preserving legal certainty and the rights of suspects. This study affirms that understanding the boundaries of corruption is important not only for law enforcement officers but also for fostering integrity awareness through anti-corruption character education